PENDIDIKAN KARAKTER MELALUI IMPLEMENTASI BUDAYA RELIGIUS DI SEKOLAH (STUDI DI SD LPI ZUMROTUS SALAMAH TULUNGAGUNG) - Makherus Sholeh (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2016)
Leadership is an important life skill. Effective and strong leadership is necessary to initiate the creation and developmet of character education through religious culture at schools in achieving their goals. There are at least two ways to develop character education through religious culture at schools: formal-structural and cultural-nonstructural. The following are the research results in Islamic Elementary School LPI Zumrotus Salamah Tulungagung (1) life characters developed there covers: obedience to Allah, being fifial to parents, loving Alquran, morality, honesty, and caring for environment. Those values are manifested in the students’ daily activities at school, such as: congregational prays(dluha, dluhur, jumat, and ashar); memorizing daily prays relating to themselves, parents, teachers, and fellow muslims; memorizing short surahs and/or two last sections of Alquran (section 29 and 30), and asmaul husna; saying salam when meeting fellow friends or when teachers greet them first, smiling, greeting, shaking hands, politeness, respecting differences and being tolerance; café of honesty; separating organic trash from non organic trash, the organic ones are put in a composter, and planting plants around the class using organic compost they made themselves. (2) The character education development is done through two approaches, habituation and modeling, at two synergic levels, schools and classroom (learning). At school level, students and teachers develop school cultures, develop disciplines, and celebrateIslamic Holidays and National Day. At school level, the character education development is integrated into curriculum, elaborated into lesson plans, then implemented.